Temporal Distribution of Gastropods In Rocky Intertidal Area In North Manokwari, West Papua - Dandi Saleky; Simon P.O Leatemia; Yuanike Yuanike; Irman Rumengan; I Nyoman Giri Putra (Jurnal Sumberdaya Akuatik Indopasifik, 2019)
Gastropods is an important organism that commonly found inhabiting the rocky intertidal area. Distribution pattern of this species is influenced by various factors such as population history, microhabitat, predation and a complex interactions between oceanographic dynamics and ecological features. This study aims to compare the temporal distribution pattern of gastropods at two different rocky intertidal area. This research was conducted at the rocky intertidal area of Amban and Nuni, North Manokwari District, West Papua. Data collection was performed during the daylight and night in April and June 2012 using systematic sampling method. The results showed that both physical and chemical factors are suite for supporting gastropods life. Furthermore, these factors seem to have an impact on gastropod zoning patterns observed in the study area. The similarity index values ​​indicate that the similarity of gastropod species between the two locations is low, which means that the species of gastropods found in each location is quite different. The community structure of gastropod at the study area is stable. In addition, we found that the gastropods diversity were higher during the night than the daylight because gastropods are classified as a nocturnal animals. Key Words: Gastropod; Rocky Intertidal; Community Structure; Nocturnal